The Urgency of Precautionary Principle in EIA Following the Enactment Omnibus Law on Job Creation - Ramlan Ramlan; Tri Hardyanthi; Suhermi Suhermi; Sasmiar Sasmiar; Mardhatillah Mardhatillah (Administrative and Environtmental Law Review, 2025)
Environmental Impact Assessment (EIA) serves as a legal instrument to evaluate the major effects of proposed businesses or activities and implement preventive measures to mitigate potential environmental impacts. Beyond being a prerequisite for environmental permits, EIA provides decision-makers with a basis for approval while incorporating the precautionary principle. Following the enactment of Law No. 6 of 2023, which formalizes Government Regulation in Lieu of Law No. 2 of 2022 on Job Creation, the precautionary principle is applied only to high-risk activities, limiting its broader role in environmental protection. This study employs a normative juridical approach to assess whether current Indonesian legislation aligns with environmental law principles. Findings indicate that post-Job Creation Law, the precautionary principle is restricted to activities with significant risks and uncertain scientific outcomes, highlighting the need for its wider application across all business activities to support sustainable development that balances economic, ecological, and socio-cultural interests.